'Nobody is going to go out there' - Plowright, Walter (Technical Centre for Agricultural and Rural Cooperation, 1999)
Walter Plowright was ultimately rewarded with the 1999 World Food Prize for the vaccine he developed that has almost made possible the elimination the cattle disease, rinderpest. At the award ceremony in London, England, in October 1999